Characterizing undrained behaviour of imperfectly saturated Palar sand - Akshaya Gangayya Ghalimath; Joseph Antony Visuvasam (Results in Engineering)
The occurrence of earthquake-induced soil liquefaction poses a significant threat, leading to extensive damage to building foundations and other structures, resulting in substantial economic repercussions. The seismic performance of geotechnical systems is markedly influenced by the saturation level of the soil. This study examines the impact of dynamic response on Palar sand. Cyclic triaxial tests were conducted on partially saturated fine-grained loose sand with a relative density of 35 % and a degree of saturation ranging from 65 % to 75 %. These tests were carried out at a strain rate of 0.1 % and confining pressures of 50 and 75 kPa. The study findings reveal that an increase in back pressure corresponds to a rise in the excess pore water pressure ratio of the sand. Additionally, the sand undergoes liquefaction as the number of cycles increases, and the degree of saturation decreases for different confining pressures at frequencies of 0.75 and 1 Hz. It was observed that soil liquefies more rapidly at lower strain rates with an increase in effective confining pressure. Conversely, at higher frequencies, soil liquefaction occurs in a smaller number of cycles. Comparing the effects of confining pressure and frequency, a damping ratio of 13 % and a shear modulus of 40 MPa were achieved at a frequency of 0.75 Hz and a confining pressure of 50 kPa. The shear modulus of partially saturated sand decreases with an increase in the initial degree of saturation due to specific characteristics of the Palar sand and the loading conditions.